Effect of education Intervention on awareness regarding breast self-examination and breast cancer among women in a rural community, Nepal. - Dhakal, Kamala; Changying,Chen (2020)
Abstract; Research entitled Effect of Education Intervention on Awareness regarding Breast Self Examination and Breast Cancer among Women in a Rural Community, Nepal Was carried out to evaluate the effect of education intervention on awareness regarding breast self-examination and breast cancer among women, in a rural community, Nepal. A True-experimental design was used to find effect of education intervention on awareness regarding breast self-examination and breast cancer among women in a rural community. The population of the study was the women of 20-60 years of age. Total 274 (137 women in Intervention and 137 women in control group) women were participated from Jwalamukhi Gaunpalika and Triuprasundari Gaunpalika Dhading district Bagmati zone, Provinance no 3. Jwalamukhi Gaunpalika was selected as an intervention group and Triuprasundari Gaunpalika was selected as a control group. Non proportionate simple ramdom sampling technique was used to select the sample through vote list of Jwalamukhi Gaunpalika and Triuprasundari Gaunpalika of Dhading district. The recruitment of participants was done by lottery method. The validity of the questionnaire items was evaluated with an Item content validity index (CVI) and content validity ratio (CVR) and the reliability was evaluated by using Cronbach's αcoefficient. Data was collected from Asar 2076 to Kartik 2076 with structured questionnaires by using face to face interview technique. Pre intervention and post intervention data were collected from both intervention and control group. Intervention was given to the respondents who were selected as intervention group (Jwalamukhi Gaunpalika). 90 minutes' two educational session was given to the respondents of intervention group after pretest. Post test data collection was done one and half months after the educational intervention among respondents of intervention and control group. The data were analyzed by using descriptive and inferential statistics. I-CVI was found more than 0.78 and S-CVI/Ave was found 0.85. CVR was found 0.8 to 1. The item wise Cronbach's Alpha was more than 0.7 and average Cronbach's Alpha was 0.89. Among 274 respondents 35.76 % and 38.68% of the respondents were below 30 years of age group in intervention and control group respectively. Respondents were from Hindu religion is 93.43% and 94.8 %, in intervention and control group respectively. The majority of respondents were from Newar, that is 31.38% and 34.30 %, respectively in intervention and control group. Regarding educational status 20.7% & 23.9% of the respondents were illiterate in intervention group and control group respectively. 87.9% and 89.28%, were married in intervention and control group respectively. Majority of the respondents were homemaker that is 79.3% and 72.14% were in intervention and control group respectively. 6.4 % & 7.9% of the respondents had experience of breast disease in intervention and control group respectively. Among the respondents who had experience of breast disease 66.66% & 36.36% of the respondents had experience of breast lump in intervention and control group respectively. Among all respondents 5.7 % and 9.29 % of the respondents had family history of breast cancer in intervention group and control group respectively. The study reviled that 96.4% of the respondents had poor awareness and 3.6% had good awareness on Breast Self Examination (BSE) in pretest whereas after education intervention 81.4% of the respondents had good awareness and only 18.6% had the respondents had poor awareness about BSE in post test. Similarly, in control group, 91. 2% of the respondents had poor awareness in pretest and 92% of the respondents had poor awareness about BSE in post test. There is significantly increased in post test awareness at 95% confidence level using chi-square test (p-value <0.001) in intervention group about awareness on BSE. Awareness in control group before and after education intervention is similar using chi-square test (p-value 0.828). Regarding practice on BSE only 1.4% had good practice and 98.6% of the respondents had poor practice on BES in pre-test but after intervention good practice increased up to 79.3% in post test in intervention group. In control group15.3% of the respondents had good and 84.7% had poor practice on BSE in pretest and 21.2% had good and 78.8 % had poor practice on BSE in post test. There is difference in practice before and after the education intervention at 95% confidence level using chi square test (p-value <0.001) in intervention group about practice on BSE. Practices regarding BSE in control group before and after is similar using chi-square test (p-value 0.673) Regarding awareness on Breast Cancer(BC) in intervention group 25.5% of the respondents had good & 74.5% of the respondents had poor awareness about BC in pretest while 67.1% of the respondents had good and 32.9% of the respondent had poor awareness about BC in post test. In control group 33.7% of the respondents had good and 64.3% of the respondents had poor awareness about BC in pretest and 23.4% of the respondents had good awareness and 76.6% of the respondents had poor awareness about BC in post test. More than 90% of the respondents of both intervention and control group had poor awareness on pretest and less than 10% of the respondents of both intervention and control group had good awareness on pretest. There is significant association between intervention and control group after education intervention in post test regarding awareness on BSE, p-value is <0.001 using chi square test. More than 80% of the respondents of both intervention and control group had poor practice and less than 20% of the respondents of both intervention and control group had good practice regarding BSE during pretest. There is significant association between intervention and control group in post test regarding practice on BSE, p-value is <0.001 using chi square test. More than 60% of the respondents of both intervention and control group had poor awareness and less than 40% of the respondents of both intervention and control group had good awareness regarding BC during pretest. There is significant association between intervention and control group in post test regarding awareness on BC, p-value is <0.001 using chi square test.